An alternative economic policy for Latin America: an urgent need - Ariza Barbosa, Nilce (Universidad Pedagógica y Tecnológica de Colombia, 2003)
The author points at the failure of the neoliberal model imposed upon Latin America. She indicates alternatives of local financing. such as the Poverty Bank as a possible way out of the crisis. She poignantly criticizes International Monetary Fund policies.